(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In 2019, Hydroquest tested its first 1MW-rated full-scale tidal turbine at Paimpol-Bréhat site. The success of this deployment has enabled the company to launch the development of the next generation of turbines through the FloWatt and Verti-Lab projects. In these projects, the validation of the industrial development tools are based on comparisons of experimental, numerical and in-situ data at both small and large scales. In this context, a 1:20 scale tidal turbine model, similar to the geometry of the demonstrator designed for deployment in the Alderney Race, is tested under representative conditions in the wave and current circulating tank of Ifremer. The experimental set-up specifically developed for this project enables synchronised measurements of performance (from the rotor torque), blade forces and flow characteristics (from 2D PIV measurement) to be carried out. The paper aims to describe in-depth the effects of fluid-structure inter- actions between the hydrodynamic loads and the blades of the turbine. To this end, we will first detail the experimental setup based on the use of a full quadrirotor twin vertical axis tidal turbine model and a single rotor de- vice. Then, we will study the angular distribution of the blade forces and the flow characteristics close to the blade for several configurations in order to analyse the effect of the different parts of the model, the central structure and the gravity base, on the rotor dynamic behaviour. The comparison be- tween the quadrirotor and the single rotor cases will help to understand the angular repartition of the blade lift and drag forces. In this way, the dynamic stall, which is typical of vertical axis tidal turbines, can be characterised from both the rotor mechanical behaviour and the dynamic of the flow around the blades. The trials are carried out in January 2025 and the data will be fully anal- ysed in February in order to be able to send the paper before end of March.